A DNA methylation profile of long non-coding RNAs can predict OS in prostate cancer. Issue 1 (1st January 2021) - Cheng, Wei; Cao, Jie; xia, Yong; Lei, Xin; Wu, Lili; Shi, Liang
ABSTRACT: Prostate cancer (PCa) is the most common male reproductive tract malignant tumor, accurate evaluation of PCa characterization and prognostic prediction at diagnosis are vital for the effective administration of the disease, especially at the molecular level. In this study, 48 CpG sites with differential methylation associated with overall survival (OS) were screened out between PCa and normal adjacent tissues. 16 CpG sites were selected by the least absolute shrinkage and selection operator (LASSO) and the risk score formula for methylated-based classifier was established. For 16-lncRNAs-CpG-classifier, the area under the curve (AUC) were 0.890, 0.917, and 0.932 at 3 years, 5 years and 7 years, respectively. Kaplan–Meier curves indicated that patients with high-risk scores had worse OS than those with low-risk scores. Prognostic methylation model of lncRNAs was identified from the whole genome in patients with PCa. This novel finding provides a novel insight for screening biomarkers of a prognosis for PCa. Graphical abstract: uf0001